Business Incubators’ Role in Startup Promotion and Economic Development : Bibliometric Analysis - Prasad, R. Sivarama; Srivastava, Abhay Kumar; Kumar, Bayya Rajesh (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : The current study provided a comprehensive record of the information structure within business incubator research. It attempted to classify existing and emerging trends, while also identifying gaps, through a systematic literature review. Methodology : We conducted a bibliometric analysis (BA) of 275 Scopus-indexed articles using VOSviewer and Biblioshiny software. This presentation outlined the field’s collaborative networks and intellectual structures, influential authors, key sources, highly cited articles, leading countries, bibliographic coupling, co-occurrence analysis, and trending topics. Findings : This study revealed significant annual publication trends, highly cited articles, prolific authors, and leading nations. Additionally, we further explained key research themes and intellectual structures through co-occurrence analysis, bibliographic coupling, thematic mapping, thematic evolution, and trending topics. Practical Implications : The research highlighted the importance of strategic resource allocation, effective network management, tailored incubation programs, sustainable practices, entrepreneurship education, and best practices. These findings provided essential guidance for managers, policymakers, and scholars. Originality : This study concluded the current literature on business incubators with an inclusive BA. It uniquely synthesized the field, identifying key research trends, prominent contributors, and policy directions, offering valuable insights for future research.